睡眠がめまいに及ぼす影響 - 中山, 明峰; 佐藤, 慎太郎; 有馬, 菜千枝; 福井, 文子 (JIBI INKOKA TEMBO, 2017)
Disfunction of Balance system, such as dizziness, may cause by multiple factors including unknown reason. It is well known that insomnia is associated with increased psychological symptomatology and perceived stress, higher predisposition to arousal, and greater impairments to quality of health. The relationship between dizziness and stress is well documented, but that between dizziness and insomnia is unclear. In this series, we focus on the Ménière's disease, which is characterized by fluctuating and progressive hearing loss, aural fullness, tinnitus, and intermittent attacks of vertigo, an illusory sensation of movement resulting from dysfunction of the labyrinth and cochlea, to investigate the relation between sleep disorders.　In our previous report, we first found that sleep quality of Ménière's disease patients was impaired. Ménière's patients have longer total sleeping time, lack of deep sleep stages, increased arousal, and were occasionally combined with obstructive sleep apnea syndrome and/or periodic limb movement disorder. Poor quality of sleep may cause additional stress and lead Ménière's disease patients to a negative spiral of symptoms. Furthermore, poor sleep quality may result in Ménière's disease patients being refractory to medical management. Therefore, prospective treatment focusing on the sleep disorders of, not just Ménière's disease but possibly dizziness symptoms, may become an additional new strategy for terminating the negative spiral of symptoms and reduce exacerbations.